#TITLE_ALTERNATIVE# - NOVELIA SUAWA (NIM : 13706020); Dosen Pembimbing 1 : Dr. Ir. Slameto Wiryolukito ; Dosen Pem, RINI
Increased demand for oil and gas leads the exploration to more agressive wells. One of the difficulties is the problem of corrosion. H2S is one of the causes of corrosion in oil and gas industry. The presence of H2S and stress can lead to a type of corrosion: Sulfide Stress Cracking (SSC). To anticipate the corrosive environments, Corrosion Resistant Alloys (CRA) can be chosen. However, the expensive price of CRA makes cladding materials are widely used. Cladding material is a combination of CRA with other materials, such as carbon steel, with low economic value but low corrosion resistance as well. In this research, characterizations of cladding pipe steel X-42 and Alloy 825 and SSC examination of the pipe are delivered; with several variables to see the effect of loading, welding, and crevice in the pipe cladding. Characterizations are completed by using OES, EDS, metallography, tensile test, bending test, and hardness test. SSC tests are carried out in accordance to NACE TM 0177-05 Standard Test Method B. Bending load with pseudo-stress of 80% of pipe yield strength is given to specimens. Solution used was Solution A (NACE TM 0177-05) and synthetic seawater (ASTM D 1141). Specimens are taken from the pipe body, seam weld, and girth weld. Specimens were tested with load; with load and holes; and without any load. Tests carried out at room temperature for 96 hours and 720 hours. After examining the SSC test results, no SSC cracks were found in all specimens: loaded; loaded and holed; and unloaded. In the holed specimens, galvanic and crevice corrosions were found, but the corrosions did not lead to SSC cracks. The good performance of the cladding pipe to encounter the SSC attacks can be caused by the elements of Alloy 825 which act together to develop strength and resistance to several types of corrosion attack.